Comparative analysis of conserved miRNAs in maize germination and vegetative development - Donayre-Torres, Alberto J. (2026)
Seed germination represents a metabolically active but transcriptionally limited transition that depends largely on post-transcriptional regulation. MicroRNAs (miRNAs) are key regulators of gene expression through mRNA slicing or translational inhibition, and may play an important role in controlling stored mRNAs during early germination. In this study, we combined bioinformatic analysis and experimental validation to identify conserved miRNAs involved in maize (Zea mays) germination. Mature miRNA sequences from Zea mays and Oryza sativa were retrieved from PMRD and miRBase v22.1, identifying conserved candidates across cereals. From this set, ten miRNAs were selected based on sequence conservation and reported roles in seed biology. Target prediction using thermodynamic modelling (ViennaRNA; MFE ≤ −25 kcal/mol) revealed potential interactions between specific miRNAs and mRNAs encoding ribosomal proteins, suggesting regulation of the translational machinery. Expression analysis by Northern blot across germination stages (0, 6, 12, and 24 h) and vegetative tissues showed distinct patterns. miR528 and miR396a were highly expressed in seeds but absent in vegetative tissues, while miR408 decreased after imbibition. miR414 and miR415 displayed transient expression during germination. Notably, miR160a was strongly expressed during germination, suggesting a role beyond vegetative development. These results support a model in which miRNAs regulate stored mRNAs and translation during germination. This work provides candidate miRNAs for functional studies and potential targets for improving seed vigor and early seedling establishment in maize.